Pulmonary Embolism in Reoperation of Alveolar Ridge Cancer: a Case Study - อนุกูลประเสริฐ, ธิตินัฐ (Journal of Health Science of Thailand, 2024)
Complications after alveolar ridge cancer surgery such as a dehiscenced wound or infected wound because this is rich of saliva organ requiring reoperation to correct these complications. In addition, deep vein thrombosis and pulmonary embolism are major postoperative complications which life threatening conditions, particularly in patients with many risk factors such as old age (>70 years old), active cancer, immobilization for more than 3 days, and infected postoperative wound. In this case report we found thrombosis in the right internal jugular vein and a massive pulmonary embolism during surgery making the patient to have unstable vital signs. It was difficult condition to decide because we could not perform definite treatment for pulmonary embolism between surgery. The use of anticoagulant might increase blood loss in the surgical field and our institute was unable to perform thrombectomy. This case study shares an experience when encounters difficult hematological condition during surgical operation.